SIZE EFFECT ON THE ULTIMATE DRYING SHRINKAGE OF CEMENT MORTAR: 1-YEAR EXPERIMENT AND NUMERICAL MODELING - Lenka Dohnalová; Petr Havlásek; Vít Šmilauer; Pavel Reiterman; Vendula Davidová (Acta Polytechnica CTU Proceedings)
The magnitude and time evolution of shrinkage are influenced by numerous factors which are implemented in the design codes often in a different way. The time-dependent behavior of concrete in structures sensitive to creep and shrinkage should be verified by means of short-term laboratory measurements. Extrapolation of drying shrinkage from short-term measurements is an illposed problem. The process is extremely slow but can be accelerated by reducing the specimen size. The knowledge of the size-effect on drying shrinkage is a necessity to establish the transition from the laboratory to the structural size. In the literature, the experimental data on such size-effect are insufficient. For this reason a new experiment was developed to study this phenomenon on small-scale specimens made of cement mortar and the results from the first year are summarized in this paper. The measured data are validated by coupled FEM hygro-mechanical simulations.